Findbuch des Bestandes Abt. 77 Dänische Ministerien - Rathjen, Jörg (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2018)
In connection with the transition of the Kingdom of Denmark from an absolutist to a constitutional monarchy in 1848, a fundamental modernisation of the administration took place at the central level. The collegial authorities that had emerged in the 16th and 17th centuries, such as the Danish Chancellery, the Schleswig-Holstein-Lauenburg Chancellery (German Chancellery) or the Chamber of Pensions, were now replaced by ministries. The new central authorities were headed by ministers who were responsible to the Reichstag. The National Archives hold only a small amount of archival material from the Danish ministries. The bulk of the archival records of the authorities listed in this finding aid are held in the Danish National Archives in Copenhagen. Only a few files of the Ministry of Justice, the Ministry of the Interior and the Ministry of the Navy can be found in the holdings of section 77. The main focus is on the records of the Ministry of Finance. Its archival records on customs mainly concern matters in Holstein and Lauenburg, but also in Lübeck; the archival records on domains and on forestry and hunting, on the other hand, relate without exception to the Duchy of Schleswig.